SU‐D‐18C‐05: Variable Bolus Arterial Spin Labeling MRI for Accurate Cerebral Blood Flow and Arterial Transit Time Mapping - Johnston, M; Jung, Y (Medical physics (Lancaster), 2014)
Purpose: Arterial spin labeling (ASL) is an MRI perfusion imaging method from which quantitative cerebral blood flow (CBF) maps can be calculated. Acquisition with variable post‐labeling delays (PLD) and variable TRs allows for arterial transit time (ATT) mapping and leads to more accurate CBF quantification with a scan time saving of 48%. In addition, T1 and M0 maps can be obtained without a separate scan. In order to accurately estimate ATT and T1 of brain tissue from the ASL data, variable labeling durations were invented, entitled variable‐bolus ASL. Methods: All images were collected on a healthy subject with a 3T Siemens Skyra scanner. Variable‐bolus Psuedo‐continuous ASL (PCASL) images were collected with 7 TI times ranging 100‐4300ms in increments of 700ms with TR ranging 1000‐5200ms. All boluses were 1600ms when the TI allowed, otherwise the bolus duration was 100ms shorter than the TI. All TI times were interleaved to reduce sensitivity to motion. Voxel‐wise T1 and M0 maps were estimated using a linear least squares fitting routine from the average singal from each TI time. Then pairwise subtraction of each label/control pair and averaging for each TI time was performed. CBF and ATT maps were created using the standard model by Buxton et al. with a nonlinear fitting routine using the T1 tissue map. Results: CBF maps insensitive to ATT were produced along with ATT maps. Both maps show patterns and averages consistent with literature. The T1 map also shows typical T1 contrast. Conclusion: It has been demonstrated that variablebolus ASL produces CBF maps free from the errors due to ATT and tissue T1 variations and provides M0, T1, and ATT maps which have potential utility. This is accomplished with a single scan in a feasible scan time (under 6 minutes) with low sensivity to motion.